Queering the Common Core (and the NGSS): Challenging Normativity and Embracing Possibility. Issue 12 (15th October 2022) - Mattheis, Allison; Lovos, Joel; Humphrey, Carly; Eichenberger, Lindsey; Nazar, Christina Restrepo
ABSTRACT: As guidelines for teacher practice, standards and benchmarks serve a strong normative purpose that can work counter to goals of equity and justice. In this project we applied queer theory's critique of normativity and concepts from queer pedagogy to the Common Core State Standards (CCSS) and the Next Generation Science Standards (NGSS). Using a collaborative qualitative approach, our research team explored and document how pre-service and practicing teachers addressed issues of learning modality, selection of diverse sources and texts, and applied the meanings of "queer" to suggest ways to disrupt traditional structures and modes of communication, in addition to including LGBTQ identities and gender and sexual diversity in their classes. We propose that queering the standards is an approach that acknowledges the material constraints that shape and characterize K-12 schools in the U.S., while also opening opportunities for teachers to engage in the crucial, intense, and necessary work to make schools sites that create rather than foreclose possibility.